Oil on Ice - Boudart, Bo; Djerassi, Dale; Coyote, Peter (Warner, 2005)
"Oil on Ice", a timely documentary directed by Bo Boudart and Dale Djerassi and narrated by Peter Coyote, examines the struggle to safeguard the Arctic National Wildlife Refuge (ANWR), a pristine19-million acre refuge located in northeast Alaska, from oil exploration and development by Native Americans and progressive conservationists. The current Bush administration, following the pattern set by the first Bush administration in 1989-90, has attempted to obtain congressional authorization for oil exploration and development in ANWR, without success. The recent re-election of George W. Bush, however, means that a Republican-controlled Congress will revisit opening ANWR to oil development in the near term ... [www.movie-vault.com]